A study of clinico pathological evaluation of acute scrotum and its management in adults in a tertiary care hospital - Al Masud, A. K. M.; Dutta, Surajit; Mandal, Prodip Kumar; Alom, Nurul (International Journal of Research in Medical Sciences, 2025)
Background: The acute scrotum is a surgical emergency. It is defined as scrotal pain, swelling, and redness of acute onset. Scrotal abnormalities can be divided into three groups, which are extra-testicular lesion, intra-testicular lesion and trauma. Acute scrotal pain, once diagnosed, can be treated appropriately with either conservative or surgical measures. The appropriate management pathway is determined by proper history taking, clinical examination and investigations in a restricted time frame. Objectives were to evaluate clinical presentation, diagnosis, management, complications, and short-term outcomes of acute scrotum, including hospital stay and mortality. Methods: A descriptive cross-sectional study was conducted at Dhaka medical college hospital from January to September 2013, including 210 adult patients (≥18 years) with acute scrotal pathology. Purposive sampling was used. Data on demographics, clinical features, investigations [complete blood count (CBC), urine routine examination (R/E), ultrasonography (USG)], management, and outcomes were collected prospectively. Statistical analysis was performed using SPSS, with results expressed as mean, standard deviation, and percentages. Results: Among 210 patients with acute scrotum, acute epididymitis (24.28%) was the most common diagnosis, followed by epididymo-orchitis (13.80%) and testicular torsion (12.38%). Most patients were aged 21-30 years (27.76%) with normal body mass index (BMI) (85.07%). Scrotal swelling (79.52%) and fever (64.76%) were predominant symptoms, while only 15.23% presented within 6 hours. Surgical intervention was required in 53% of cases, with debridement (22.86%) being the most common. The mean hospital stay was 1.34 weeks, with 66.70% discharged within a week. Conclusions: Acute scrotum requires urgent diagnosis and treatment; surgery for torsion and trauma, conservative care for infections ensures better outcomes.